Extension officers’ perceptions of extension and innovation in South Africa - Davis, Kristin E.; Landini, F.; van Niekerk, J.; Green, K.; Terblanche, S. E. (Academy of Science of South Africa, 2019)
Extension is evolving, and extension workers’ roles and attitudes are changing with global realities. The purpose of this study was to examine South African extension officers’ perceptions of their job, views on the objectives of extension, and conception of agriculture. A questionnaire was developed consisting of general demographic and Likert-scale questions regarding perceptions of extension. The survey was emailed to all South African based members of the South African Society for Agricultural Extension (SASAE). The study found that most extensionists considered extension as a professional or technical practice to improve farmer practices followed by those who consider it as “helping farmers” to improve their well-being. The most preferred methods and the area of actual practice were first group and second individual approaches. According to the respondents, productive modernisation aimed at productivity and profitability was the highest extension objective, followed by increasing farmers’ knowledge through training. In addition, results provide evidence that extension institutions tend to support conventional agriculture, while extension workers are more concerned with potential negative impacts. Finally, the Likert-scale responses show that while much South African extension work is based on dialogue and horizontal coordination using a participatory approach, transfer of technology still exists, and farmers are blamed for their problems.